The evolution of the concept of aging and old age. Will we finally talk about health in old age in the 21st century? - Gutiérrez, Bruno (2022)
Population aging is a reality, the demographic and epidemiological transition poses a differential challenge to society in the aging process. The 2020-2030 decade has been called healthy aging, a concept that must be seen in the light of information, life and health. This article seeks to give a different look at what this concept implies from the elderly person, a development of 4 central ideas is made on the subject, the transition of aging and old age, the concept of health in old age, aging from the positive within the framework of active and healthy aging and information as part of health and aging. The person over his sixth decade has gone through multiple historical and social developments, entropic situations and unexpected learning, which make him an ideal population for the implementation of healthy aging, perhaps the main question is ¿Who could talk about it? a question that requires health preparation and a paradigm shift from pure positivist understanding of the person as a complex, critical and changing being.